Identifying the Species of Seeds in Traditional Chinese Medicine Using DNA Barcoding - Xiong, Chao; Sun, Wei; Li, Jingjian; Yao, Hui; Shi, Yuhua; Wang, Ping; Huang, Bisheng; Shi, Linchun; Liu, Di; Hu, Zhigang; Chen, Shilin (Frontiers in Pharmacology, 2018)
Seed is not only the main reproductive organ of most of herbal plants but also an important part of Traditional Chinese Medicine (TCM). Seed TCMs possess important medicinal properties and have been widely used as components of pharmaceutical products. In parallel with the increasing popularity and accessibility of seeds as medicinal products in recent years, numerous substitutes and adulterants have also appeared on the market. Due to the small volume and similar appearances of many seed TCMs, they are very difficult to accurately identify the constituent plant species through organoleptic methods. Usage of the wrong herb may be ineffective or may worsen the condition and even cause death. Correct identification of seed herbal medicines is therefore essential for their safe use. Here, we acquired 177 ITS2 sequences and 15 psbA-trnH sequences from 51 kinds of seed TCMs belonging to 64 species that have been described in the Chinese Pharmacopoeia. Tree-building analysis showed that the ITS2 sequences of 48 seed TCMs can be differentiated from each other, and they formed distinct, non-overlapping groups in the ML tree. Furthermore, all of the sequences acquired in this study have been submitted to the public DNA barcoding system for herbal medicine, and this integrated database was used to identify 400 seed TCM samples purchased from medicinal markets, drug stores, and the Internet, enabling the identification of 7.5% of the samples as containing non-declared species. This study provides a brief operating procedure for the identification of seed TCMs found in herbal medicine. In the future, researchers and traditional herbal medicine enterprises can use this system to test their herbal materials.